TANGGUNG JAWAB PENGELOLA TEMPAT WISATA TERHADAP KERUGIAN KONSUMEN BERDASARKAN UNDANG-UNDANG NOMOR 8 TAHUN 1999 TENTANG PERLINDUNGAN KONSUMEN (STUDI PUTUSAN NOMOR 186/PDT.G/2018/PN.MLG) - Tara Ulina Ginting; Amad Sudiro (Fakultas Hukum Universitas Tarumanagara, 2020)
The consumer protection law that regulated in by the law number 8 of 1999 concerning consumer protection. rights and obligations of consumers as well as responsibilities of business actors are part of it. If a consumer experiences injuries to his body parts that cause his rights and obligations to be harmed, that is where the law must be enforced fairly. so that the relationship between consumers and business actors is mutually binding. so that the implementation of responsibility for managing tourist attractions against consumer losses can be resolved. There are 4 forms of responsibility, namely product responsibility, clear honesty and accurate information, protecting consumers well, providing quality goods and services, providing appropriate forms of compensationLaw number 10 of 2009 concerning tourism regulates how the rights of each tourist contain accurate information about tourist attractions, tourism services in accordance with standards, legal protection and security, health services, protection of personal rights and insurance protection for tourism activities high risk.